Acute hepatitis A infection after hepatitis A immunity in a HIV-positive individual. (31st August 2017) - Lee, Ming Jie; Douthwaite, Sam; Kulasegaram, Ranjababu
Abstract : Hepatitis A is a self-limiting infection caused by the hepatitis A virus (HAV), transmitted predominantly by the faecal–oral route including some sexual practices. Outbreaks are commonly reported in the men who have sex with men (population. Previous exposure is thought to provide life-long immunity against subsequent infections with the development of an HAV IgG response. This paper reports a case of acute Hepatitis A infection, despite evidence of a previously positive Hepatitis A IgG results in an HIV-positive individual.